2008
DOI: 10.1080/09243450802332184
|View full text |Cite
|
Sign up to set email alerts
|

Response of school personnel to student threat assessment training

Abstract: School safety has become an important area of concern for school improvement. This study examined the effects of staff training as means of improving school responses to student threats of violence. A multidisciplinary sample of 351 staff from 2 school divisions completed pre-post training surveys as part of a 1-day training program using the Guidelines for Responding to Student Threats of Violence (Cornell & Sheras, 2006). Analysis of pre-post surveys found large changes in staff attitudes toward school safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
(34 reference statements)
7
25
0
Order By: Relevance
“…These results are consistent with other studies of threat assessment. For example, evaluation studies of the Virginia Student Threat Assessment Guidelines in the United States have shown that 1‐day staff training has a substantial effect on the attitudes and knowledge of school personnel across disciplines, including school principals, psychologists, counselors, social workers, and school‐based police officers (Allen, Cornell, Lorek, & Sheras, ; Cornell, Allen, & Fan, ), including substantial changes in knowledge and attitudes regarding school violence, school discipline, and threat assessment.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with other studies of threat assessment. For example, evaluation studies of the Virginia Student Threat Assessment Guidelines in the United States have shown that 1‐day staff training has a substantial effect on the attitudes and knowledge of school personnel across disciplines, including school principals, psychologists, counselors, social workers, and school‐based police officers (Allen, Cornell, Lorek, & Sheras, ; Cornell, Allen, & Fan, ), including substantial changes in knowledge and attitudes regarding school violence, school discipline, and threat assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The Virginia Guidelines represent a threat assessment approach to school discipline that is intended in part to give school authorities an alternative to zero tolerance when students engage in threatening behavior. Two studies found that training school administrators (and other school staff) in the use of threat assessment reduces their support for zero tolerance and school suspension (Allen, Cornell, Lorek, & Sheras, ; Cornell et al., 2012). In addition, three studies have found that schools adopting the Virginia Guidelines have reductions in their suspension rates (Cornell, Gregory, & Fan, 2011; Cornell, Sheras, Gregory, & Fan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the training stressed that students who threatened to kill someone did not need to be given a long-term suspension, and that almost all students who made such threats could continue in school, provided that the threat assessment procedures were followed. A study of workshop participants showed large improvements in staff attitudes toward threat assessment principles and decreased endorsement of zero-tolerance approaches after training (Allen et al, 2008).…”
Section: Explanations For Study Findingsmentioning
confidence: 99%